Violência interpessoal contra a criança: uma análise dos casos notificados no Espírito Santo - Pedroso, Márcia Regina de Oliveira (2022)
Introduction: Violence in childhood is a worldwide public health problem that causes physical, mental and emotional damage to victims, impacting their quality of life and their performance in adulthood. Despite the existence of childhood protection policies, children continue to be victims of violence, thus highlighting the importance of studies to identify its prevalence and to understand this phenomenon. Objective: To analyze cases of interpersonal violence against children reported from 2011 to 2018 in the state of Espírito Santo. Methods: Cross-sectional study where reported cases of violence against individuals aged 0 to 9 years and registered in the Information System for Notifiable Diseases (SINAN) of Espírito Santo were analyzed. Descriptive data analysis was performed, with calculations of relative and absolute frequencies and 95% confidence intervals. In the bivariate analysis, Pe -Square test was used, and (PR). Results: Sexual violence was the most reported type, reaching a prevalence of 41.8% (95%CI: 40.0-43.5); this problem was more frequent in girls, aged from 3 years, in white children, residents of the urban area; the aggressors were mainly men and the . Neglect was recorded in 31.3% (95%CI: 29.7-33.0) of the notifications, being more prevalent in boys, aged 0 to perpetrators. The prevalence of physical violence was 23.6% (95%CI: 22.2-25.2), being associated with males, aged 6 to 9 years, rural areas, with perpetrators aged 20 years or more, it also occurred outside the residence and in night/dawn shift. Recurrent violence was present in 32.5% (95%CI: 30.8-34.1) of the notifications, being associated in boys with the age of the victim and agressor and the occurrence at home; in girls, it was with the aggressor, anf the occurrence at home. Conclusion: Violence reached a significant number of children in Espirito Santo, being the most prevalent sexual tipology, followed by neglect and physical violence. The characteristics of the victim, the aggressor and aggression associated differed between the types, but in general, the violence occurred in the hom These data demonstrate the need for advances in public policies for the protection of children, since they continue to be victims of violations of their fundamental rights. Given the 9 numerous social, economic and cultural factors involved in the etiology of violence against children, effective coordination between the diferente sectors of civil society and the state is essential. The health sector has a fundamental role, being also one of the main articulators of actions against violence, acting not only in the care of victims, but also in the prevention of this problem. However, for its objectives to be achieved, actions are needed that promote greater articulation between the diferente levels of care and also with other sectors such as education, social assistance and public security. The training of professionals to deal with violent situations, especially against children, becomes essential for the qualification of care and attention to victims; in this aspect, the importance of including the theme of violence in the curricula of all graduate courses in the health area and the establishment of permanent and continuing education actions with health professionals is highlighted. The improvement of the notification process is also essential, since this is the main instrument that triggers the care line, in addition to serving as an instrument for analyzing the condition and developing public policies. Only from these actions and the commitment of all sectors of society will it be possible to carry out effective changes that guarantee the rights of children.